BULLYING AMONG HIGH SCHOOL STUDENTS OF PUBLIC STATE SCHOOLS IN THE CITY CANTO DO BURITI-PI. (Fiep Bulletin - online, 2016)
Bullying is characterized by acts of physical or verbal violence that occur repeatedly and intentionally against one or more victims. This phenomenon has been increasing all over Brazil, therefore the need of investigation of this subject among students of public state schools in the city of Canto do Buriti-Pi. The purpose of this study was to analyze the occurrence of bullying and cyberbullying among students of the Unidade Escolar Nonato Valente and of the Unidade Escolar Beija Valente Unit. It was held a direct descriptive field research with a quantitative approach. The sample by convenience made of 280 students of both sexes aged from 13 to 18 years old in the high schools mentioned before. It was applied an 11 closed questions form to the students, about bullying its consequences and implications in the school context, on which were observed the results from the survey about the knowledge of bullying and cyberbullying inside and outside the school . In this research, it was found that 90% of students know about bullying. It was also observed that male students have committed more aggressions than female students and that most students (68%) is aware of the consequences that these physical, moral and virtual aggression can generate.
Keywords: Bullying. School. Consequences.